WoundsWest education: taking the evidence on wounds to the clinician - Carville, Keryln; Keaton, Juliet; Rayner, Robyn; Prentice, Jenny; Santamaria, Nick (Cambridge Media, 2009)
The WoundsWest (WW) education programme is an innovative and ambitious subproject of the WW project in Western Australia (WA). It involves the interdisciplinary development of online wound management education modules, which are designed to assist health professionals and health services to reduce preventable wounds and adverse wound management outcomes. The aims, objectives and processes that underpin this development are outlined in this paper, which is illustrated with examples from the WW online education programme.